2014
DOI: 10.1037/a0034374
|View full text |Cite
|
Sign up to set email alerts
|

School readiness of children from immigrant families: Contributions of region of origin, home, and childcare.

Abstract: Children from immigrant families make up a growing proportion of young children in the United States. This study highlights the heterogeneity in early academic skills related to parental region of origin. It also considers the contributions of early home and nonparental care settings to the diversity in early academic performance. Using nationally representative data from the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B; N ≅ 6,850), this study examines associations between parental region of origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 90 publications
4
47
0
1
Order By: Relevance
“…These beliefs are related to differences in early reading practices in the home environment (Jung, Fuller, & Galindo, 2012). Indeed, Koury and Votruba-Drzal (2014) have shown that there are differences in several aspects of children's home environments related to parental region of origin, including the provision of cognitive stimulation and emotional support. Based on prior research that shows that center-based EEC is associated with the greatest cognitive skills gains among children from less advantaged home environments (Bradley, McKelvey, & Whiteside-Mansell, 2011;Magnuson et al, 2004;Votruba-Drzal et al, 2013), we hypothesize that there may be variability in the implications of center-based EEC experiences based on parental region of origin.…”
Section: Heterogeneity Among Children Of Immigrantsmentioning
confidence: 96%
“…These beliefs are related to differences in early reading practices in the home environment (Jung, Fuller, & Galindo, 2012). Indeed, Koury and Votruba-Drzal (2014) have shown that there are differences in several aspects of children's home environments related to parental region of origin, including the provision of cognitive stimulation and emotional support. Based on prior research that shows that center-based EEC is associated with the greatest cognitive skills gains among children from less advantaged home environments (Bradley, McKelvey, & Whiteside-Mansell, 2011;Magnuson et al, 2004;Votruba-Drzal et al, 2013), we hypothesize that there may be variability in the implications of center-based EEC experiences based on parental region of origin.…”
Section: Heterogeneity Among Children Of Immigrantsmentioning
confidence: 96%
“…Previous research has shown that several family factors are associated with early achievement of children in immigrant families: (a) socioeconomic status (SES) (Han, 2008;Han et al, 2012), (b) parent acculturation, especially in the domain of English proficiency (Han et al, 2012), and (c) parenting practices (Koury & Votruba-Drzal, 2014). Applied to the bioecological framework, these family factors reflect both proximal processes (e.g., parent-child relationship and parenting) and aspects of the exosystems (e.g., SES, family's ethnic and cultural backgrounds) that can shape children's academic development.…”
Section: The Role Of Effortful Control In the Links Between Family Famentioning
confidence: 99%
“…For example, Chinese parents have children with a .783 advantage in early math skills, which is distinct from Filipino children (.145) and Korean children (.287) in our results but are often grouped together as "Asian" or "East Asia/ Pacific Islands" in other studies (e.g., Koury and Votruba-Drzal 2014). Likewise, the evidence for an emergent Vietnamese advantage, when socioeconomic and parenting advantages are accounted for (.290), would go unnoticed if classified under "Other Asians" (e.g., Sun 2011).…”
Section: Asian Subgroup Analysesmentioning
confidence: 61%